COUNSELING AND TRAINING OF INTERVENTION MODEL LOCAL PLANTS TO OVERCOME STUNTING (TALAS) FOR HEALTH WORKERS AT MONTASIK HEALTH CENTER, ACEH BESAR - Tahara Dilla Santi; Aditya Candra; Radhiah Zakaria (RADJA PUBLIKA, 2024)
The counseling and training activities carried out at the Montasik Health Center aim to increase insight and knowledge about the use of herbal plants in an effort to reduce stunting cases in the Montasik Health Center work area which can improve public health. Community service activities carried out by lecturers and students are a